EVALUASI SIFAT SENSORIS SARI BIJI KECIPIR (Psophocarpus tetragonolobus L.) DENGAN VARIASI WAKTU BLANCHING DAN RASIO BIJI KECIPIR DAN AIR - , RIZKA RAKHMAWATI; , Prof. Dr. Ir. Agnes Murdiati, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Nowadays, the consumption of protein has decreased. One way that can be done to increase the protein intake is by the utilization of winged bean seeds (Psophocarpus tetragonolobus L.). This research aims to create a winged bean seed extract through a variety of panelists preferred by the time of blanching and ratio winged bean seed and water. The specific objective of this study is to reduce the activity of lipoxygenase enzymes by blanching process, make winged bean seeds extract with ratio winged bean seed and water are preferred by the panelists, to reduce the unpleasant aroma of winged bean seed extract with the addition of flavor, determine the content of protein, water, fat, ash, carbohydrate of winged bean seed extract that panelists preferred and compare with the requirements of SNI of soymilk. Winged bean seeds are used Psophocarpus tetragonolobus L. Winged bean seed extract is made by blanching time variation (0, 2.5, 5, 7.5, 10 min)